Peace, Security and other Developmental Problems in Nigeria: Taxation as the Light at the End of the Tunnel - Olokooba, Saka Muhammed; Muritata, Awodun; Adebowale, Hassan I. (NIU Journal of Humanities, 2017)
The elusive and precarious nature of peace, security and development in Nigeria today is at an alarming rate. Series of criminality and criminal tendencies in form of religious, economic as well as socio-political upheavals now takes the central stage in the Nigerian polity devoid of any known common solutions. Using doctrinal research method, this paper examines the issue of peace, security and developmental problems in Nigeria. The paper posits and argues that using and applying functional as well as equitable tax on the derivative revenue foundation and sharing formula by Nigerian government, most of the associated problems with peace, security and development in Nigeria will be a thing of the past. To actualise this position, the paper proffers some practical solutions in form of recommendations.